Desarrollo de un sistema de información web para la gestión y manejo de inventarios de la IPSI Outtajiapulee en Uribía la Guajira (2023)
The project consists of developing a web-based information system for IPSI Outtajiapulee, with the aim of efficiently managing and controlling the inventory of products and supplies. The project will be carried out in 4 Sprints, using the Scrum methodology and free software tools such as Python, Django, and MySQL. During the first sprint, the objectives, scope, and requirements of the system will be established, the inventory management needs of the IPSI will be identified, and the Product Backlog will be created. In the second sprint, the graphical interface will be designed, and the features of the inventory registration and control system will be specified. In the third sprint, the inventory registration and control functionality will be developed, and an alert system will be implemented. In the fourth sprint, the report generation and data analysis functionalities will be integrated, and tests of the implemented functionalities will be carried out.